Pengaruh Kepemimpinan, Kompetensi Sumber Daya Manusia, dan Budaya Organisasi Terhadap Pengelolaan Risiko Pemeriksaan Oleh Badan Pemeriksa Keuangan Republik Indonesia - Bety Erlya Putri; Hasan Rachmany (Reformasi Administrasi, 2025)
The risk identified by the Audit Board (BPK) of the Republic of Indonesia in conducting its duties and responsibilities is audit risk, which refers to the risk of failing to meet audit standards. The Audit Team must collectively possess the necessary knowledge, experience, and competence for conducting audits. This research aims to evaluate the combined effect of leadership, human resource competence, and organizational culture on audit risk management at the Audit Board (BPK) of the Republic of Indonesia. The research approach used is quantitative, with the method involving a survey where the researcher distributed questionnaires to collect data. The conclusion of this research is that leadership, human resource competence, and organizational culture have a strong relationship with audit risk management, and together they show a positive and significant impact. Leadership had a statistical variable result of 61%, human resource competence had a statistical variable result of 56%, and organizational culture had a statistical variable result of 70% on audit risk management. Based on partial testing, it can be concluded that the effect of leadership, human resource competence, and organizational culture on audit risk management is 91%, while the remaining 9% is affected by other factors not included in this research.